The Roles of Gasdermin D in Coronavirus Infection and Evasion - Liu, Xiang; Ding, Shihao; Liu, Pinghuang (Frontiers in Microbiology, 2021)
Pyroptosis is lytic, programmed cell death and plays a critical role against microbial invasion, functioning as an innate immune effector mechanism. The pore-forming protein gasdermin D (GSDMD), a member of gasdermin family proteins, is a primary effector of pyroptosis. The cleavage of inflammasome-associated inflammatory caspases activates GSDMD to liberate the N-terminal effector domain from the C-terminal inhibitory domain and form pores in the cellular plasma membrane. Emerging evidence shows that the pore-forming activity of GSDMD beyond pyroptosis and modifies nonlytic cytosolic protein secretion in living cells and innate immunity. While the essential roles of GSDMD in bacterial infection and cancer have been widely investigated, the importance of GSDMD in virus infection, including coronaviruses, remains elusive. Here, we review the current literature regarding the activation and functions of GSDMD during virus infections. Last, we further discuss the roles of GSDMD and the therapeutic potential of targeting this GSDMD pore-forming activity in coronavirus diseases.